Dual Spaces of Multiparameter Local Hardy Spaces. (3rd December 2021) - Ding, Wei; Yu, Feng
Abstract : In this paper, we study the duality theory of the multiparameter local Hardy spaces h p ℝ n 1 × ℝ n 2, and we prove that h p ℝ n 1 × ℝ n 2 ∗ = cm o p ℝ n 1 × ℝ n 2, where cm o p ℝ n 1 × ℝ n 2 are defined by discrete Carleson measure. Moreover, we discuss the relationship among cm o p ℝ n 1 × ℝ n 2, Li p p ℝ n 1 × ℝ n 2, and rectangle cm o rect p ℝ n 1 × ℝ n 2 .